A case study about inventory management: Economic order quantity model implementation at Majlis Perbandaran Selayang / Mohd Arif Farhan Abd Wahab - Abd Wahab, Mohd Arif Farhan (Faculty of Business and Management, 2010)
This research proposal was prepared for Miss Zuraini bte Jusoh related to my research about the improvement of inventory management at Majlis Perbandaran Selayang. I choose this issue because, nowadays, excellent organization must have strong inventory to achieve in competitive business challenge. As we know, government sector in Malaysia is too behind for improvement compared to the privates because of the hurdles and barriers occurs in this sector such as bureaucracy problems, corruption and lack of technology, inadequate training and the attitude of the person itself that work for government. As a student that have been helped by this sector, i try my best to give some opinion and make some research to improve one of the Operations management view, Inventory Management to help my local government (Majlis Perbandaran Selayang) to improve their inventory management. I have minimized my scope into EOQ models that contains in inventory management. To make it not so complicated, i choose A4 papers (white) as my research items that need to be develop its EOQ models. To make this research become a successful research, the method of analyzing secondary data such as demand for A4 papers (W) at MPS, Annual budget, and some feedback from the store keeper were used. To have a good conclusion and give the best output to make a decision on improving the inventory management at MPS, an EOQ models were developed and compare it with the actual situation whether it match or not to have an EOQ model on inventory management at MPS. I hope this research will help MPS to improve their inventory management to make them become more efficient and effective on their way to manage selayang city. Besides that, I hope the entire negative taught about the government sector weak management will be shut and this improvement also can effect on the improvement of life at my city, Selayang.